UNLEASHING ENGLISH FLUENCY: HARNESSING TIKTOK'S POWER FOR SPEAKING SKILLS - Abdur Romsi; J. Priyanto Widodo; Hasan Basri; Yuliyanto Sabat; Sipulyono Sipulyono (Magister Scientiae, 2023)
English fluency is essential for effective communication in today's globalized world. Traditional language learning methods are primarily classroom-based, but technological advances and the ubiquity of social media platforms have opened up new avenues for language acquisition. This study aimed to explore TikTok outstanding potential, a popular platform (social media) lately, as a tool to improve English skills. The study applies a qualitative research design and uses a phenomenological lens to explore the EFL Teacher and learner experience and evaluate TikTok’s effectiveness to improve the fluency in English speaking skills. Moreover, results from an interview with an EFL teacher and focus group interviews with students highlight TikTok's positive impact on integrating authentic content in language learning. Additionally, the EFL teacher has found TikTok helpful in providing content relevant to the national curriculum. Besides, students report that their English vocabulary, pronunciation, and motivation to practice their English speaking have improved, and they were so happy with TikTok. However, barriers identified include limited internet and mobile phone access for some students. Overall, TikTok is an effective tool for improving English skills, allowing learners to expose themselves to great content and materials across the globe. These findings contribute to the field of language teaching, providing insights for educators and learners looking for innovative ways to improve English proficiency by leveraging technology development.